How to Read Genesis - Longman, Tremper, III. (Downers Grove, Ill. : InterVarsity Press, 2005)
"In How to Read Genesis Tremper Longman provides a welcome guide to reading and studying, understanding and savoring this panorama of beginnings - of both the world and of Israel.
And importantly for Christian readers, we gain insight into how Genesis points to Christ and can be read in light of the gospel."--Jacket.
Understanding the book of "beginnings" -- Who wrote Genesis? -- The shape of the book of Genesis -- Myth or history? : Genesis and the Enuma elish -- Noah and Utnapishtim : whose flood story should we trust? -- Abraham and Nuzi : patriarchal customs in their cultural context -- The primeval history : Genesis 1-11 -- The patriarchal narratives : Genesis 12-36 -- The Joseph story : Genesis 37-50 -- The christological difference.
Includes bibliographical references (pages 181-187) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc